Non-Performing Financing pada Bank Umum Syariah dengan Faktor Determinan ROA, BOPO, CAR, dan FDR - Fatmi Hadiani; Elva Oktavia Sari (Journal of Applied Islamic Economics and Finance, 2023)
Islamic banks engage primarily in the distribution of funds through financing activities, which inherently exposes them to financing risks. One such risk is non-performing financing, which refers to the inability of the bank to collect back the financed amount. This research aims to examine the impact of four variables, namely CAR, ROA, FDR, and BOPO, on the non-performing financing of Islamic Commercial Banks during the period of 2015-2020. The study employs a quantitative approach and utilizes panel data regression analysis. The data used for analysis are obtained from the financial statements of each Islamic Commercial Bank. The findings indicate that when considered together, CAR, ROA, FDR, and BOPO have a significant positive influence on non-performing financing. However, when analyzed individually, CAR and BOPO do not have a significant impact on non-performing financing. Conversely, the ROA variable demonstrates a significant negative effect on non-performing financing, while FDR exhibits a significant positive effect.